Emociones generadas en el proceso de observación de aula entre pares (2021)
The classroom observation process is a widely used strategy for the qualification and improvement of the teacher, however, little has been investigated regarding the emotions that the observed teacher feels and how it can influence their performance during the observation, for this reason, the objective of the research was to thought on the emotions generated in observed teachers by academic peers. For this, a thematic unit of chemistry and mathematics areas was selected to be observed continuously, writing down the findings seen in the classroom processes from an observation matrix, then feedback and reflection was carried out among the participating academic pairs. Before, during and after the observation, emotions such as expectation, anxiety, insecurity, satisfaction, feeling challenged, among others, were reported. The reflection allowed to conclude that the teaching exercise is an act that will always have spectators (students), and even so the teacher does not feel intimidated, this changes when the observer is an academic pair, it generates various emotions that invite reflection on their profession. This allows to propose researches that look for factors that can influence the observation process, for example the emotions of the observed.